(untitled) (Vietnam Journal of Community Medicine, 2024)
Objectives: Describe the current state of compliance with surgical hand hygiene procedures among surgeons at Thong Nhat Hospital in 2022. Subjects and Methods: A cross-sectional study with a quantitative design was conducted through camera observations extracted at the end of each day. The evaluation tool was a checklist designed on Google Forms based on Decision 3916/2017/QD-BYT of the Ministry of Health dated August 28, 2017. A total of 115 surgical hand hygiene instances by surgical staff were observed. Results: The overall compliance rate with the surgical hand hygiene procedures according to Decision 3916/2017/QD-BYT was 52.2%. The compliance rate for the content of each step observed was 48.6%, with step 1 having a compliance rate of 89.6%, step 2 at 80.6%, step 3 at 68.1%, step 4 at 93.1%, and the steps “Rubbing the thumb” and “Rubbing the fingertips” had the lowest compliance rates. Compliance with the time standards for the observed surgical hand hygiene opportunities was 47.2%, with the standard "First hand wash for at least 1 minute and 30 seconds" having the highest compliance rate of 80%, and the standard "Second hand wash for at least 1 minute and 30 seconds" having the lowest compliance rate of 76%. Conclusion: The compliance rate for surgical hand hygiene with antiseptic soap according to the guidelines in Decision 3916/2017/QD-BYT of the Ministry of Health dated August 28, 2017, at Thong Nhat Hospital was 52.2%.